2018
DOI: 10.1126/scitranslmed.aao0540
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of cochlear neurons activates the auditory pathway and restores auditory-driven behavior in deaf adult gerbils

Abstract: Cochlear implants partially restore hearing via direct electrical stimulation of spiral ganglion neurons (SGNs). However, spread of excitation from each electrode limits spectral coding. We explored the use of optogenetics to deliver spatially restricted and cell-specific excitation in the cochlea of adult Mongolian gerbils. Adeno-associated virus carrying the gene encoding the light-sensitive calcium translocating channelrhodopsin (CatCh) was injected into the cochlea of adult gerbils. SGNs in all cochlea tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
195
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(216 citation statements)
references
References 46 publications
7
195
2
1
Order By: Relevance
“…When increasing stimulus rate, oABR amplitudes declined (Fig G) and latencies prolonged (Fig G and I). However, in contrast to our previous reports on (i) ChR2: where potentials were found only up to 70 Hz (Hernandez et al , ) and (ii) CatCh: up to 200 Hz, and f‐Chrimson: up to 250 Hz (respectively Wrobel et al , ; Mager et al , ), we could detect sizable P 1 ‐N 1 up to stimulus rates of 500 Hz for Chronos (Fig G left, H) and 1,000 Hz for Chronos‐ES/TS (the highest stimulus rate tested in our experiments, Fig G and H). P 1 latency increased with higher stimulus rates in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…When increasing stimulus rate, oABR amplitudes declined (Fig G) and latencies prolonged (Fig G and I). However, in contrast to our previous reports on (i) ChR2: where potentials were found only up to 70 Hz (Hernandez et al , ) and (ii) CatCh: up to 200 Hz, and f‐Chrimson: up to 250 Hz (respectively Wrobel et al , ; Mager et al , ), we could detect sizable P 1 ‐N 1 up to stimulus rates of 500 Hz for Chronos (Fig G left, H) and 1,000 Hz for Chronos‐ES/TS (the highest stimulus rate tested in our experiments, Fig G and H). P 1 latency increased with higher stimulus rates in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…This would equate to at least 48 channels for the human cochlea 44 and ∌8-12 for the rat 45 . At the same time, the most efficient pulse duration for optogenetic stimulation which depends on the kinetics of the opsin of choice (0.5-2 ms 24,28,29 ) exceeds that of electrical stimulation (typically below 100 ”s 46 ). Moreover, the synchrony of optogenetically driven SGN firing 24,28,29 is lower than that of electrical stimulation [47][48][49] and closer to physiological sound stimulation 24,28,29 .…”
Section: Sound Coding Strategymentioning
confidence: 99%
“…The setup was identical as previously used in studies of optogenetic stimulation via optical fibre involving Mongolian gerbils 24 . Briefly, the ShuttleBox is composed of two platforms and a hurdle between them.…”
Section: Behavioural Experiments Setupmentioning
confidence: 99%
“…Optical CIs have the potential to drastically improve frequency and intensity coding since light can be spatially confined more conveniently. Indeed, recent studies (Hernandez et al , ; Mager et al , ; Wrobel et al , ) have demonstrated improved frequency resolution and larger output dynamic range of cochlear optogenetic stimulation over monopolar electrical stimulation. However, the first study also highlighted a low temporal fidelity of optical stimulation due to the slow closing of channelrhodopsin (ChR) after light off, leading to a breakdown of neural population responses for stimulation above 100 Hz (Hernandez et al , ).…”
mentioning
confidence: 99%
“…However, the first study also highlighted a low temporal fidelity of optical stimulation due to the slow closing of channelrhodopsin (ChR) after light off, leading to a breakdown of neural population responses for stimulation above 100 Hz (Hernandez et al , ). Although better temporal coding with selective viral expression of the ChR2‐variant CatCh in SGNs has been reached (Wrobel et al , ), achieving physiological spike rates of several hundreds of Hz and ÎŒs spike time precision has remained an important objective.…”
mentioning
confidence: 99%